Do Parental Networks Pay Off? Linking Children's Labor-Market Outcomes to their Parents' Friends - Erik Plug; Bas van der Klaauw; Lennart Ziegler (Institute for the Study of Labor (IZA), 2015)
This paper examines whether children are better off if their parents have stronger social networks. Using data on high-school friendships of parents, we analyze whether the number and characteristics of friends affect the labor-market outcomes of children. While parental friendships formed in high school appear long lasting, we find no significant impact on their children's occupational choices and earnings prospects. These results do not change when we account for network endogeneity, network persistency and network measurement error. Only when children enter the labor market, we find that friends of parents have a marginally significant but small influence on the occupational choice of children.
Keywords: A14; J24; J46; J62; 330; social networks; occupational choice; informal job search; intergenerational effects